(untitled) (Revista Electrónica REDINE, 2018)
Considering that the current changing world in which we live demands the existence of a social transformation of the individual, it is necessary to develop their intellectual, attitudinal and methodological as a way to address this reality in an interdisciplinary approach through interaction subject - object where the teacher and classroom researcher and manager relates to the object that is to form the symbolic elements of social context in the process of reconstruction and transformation of thought, action, knowledge, and therefore of himself and his reality. This essay focuses on the integration of various disciplines that can express the impact on modes of knowledge production to make way for a new dimension in the context of management education to social transformation.